Uji Tantang Bakteri Bacillus Kandidat Probiotik secara Invitro terhadap Bakteri Vibrio harveyi - Sumardi Sumardi; Salman Farisi; Christina Nugroho Ekowati; Rizka Oktavia (Jurnal Biologi Papua, 2019)
This study aims to isolate Bacillus that can fight the growth of Vibrio harveyi . Based on the results of the inter-Bacillus competition test show that Bacillus isolates was able to compete and grow with each other on the SWCA media. The challenge test Bacillus bacterial to against Vibrio harveyi bacteria, that Bacillus did not yet produce anti-bacteria on the second day. In the joint culture test method between Bacillus and Vibrio harveyi that Bacillus were able to inhibit the growth of Vibrio harveyi bacteria on the 4th day.